THE DECISION ON APPROVAL OF UNILATERAL DECLARATION OR FRIENDLY SETTLEMENT OF THE EUROPEAN COURT OF HUMAN RIGHTS AS A GROUND FOR EXCEPTIONAL REVIEW WITH A NEW CIRCUMSTANCE IN THE RA CRIMINAL PROCEDURE - Vardanyan, Arnold; Hovhannisyan, Armen (State and Law, 2021)
In the submitted article, the authors discussed the conceptual issues of cosideration the decision on approval of unilateral declaration or friendly settlement of the European Court of Human Rights as a ground for exceptional review with a new circumstance in the RA Criminal Procedure. Based on the researches of the relevant international standards and practice of other states, the authors concluded that, as an opportunity to ensure restitutio in integrum, the ruling of the European Court of Human Rights on the approval of a unilateral statement or friendly settlement, which is the result of the state's recognition of the fact of violation of a person's right provided for in an international treaty of the Republic of Armenia, should in any case be considered in a criminal legal proceedings of the Republic of Armenia as a basis for an exceptional review on a new circumstance.
Keywords: unilateral declaration; friendly settlement; European Court of Human Rights; new circumstance